Religion, culture and food waste behavior among Muslim consumers in Selangor - Abdul Wahab, Mohd Faisal; Talhah, Hasiful Fata; Zamry, Nuryn Nazura (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Food waste has been considered as a worldwide problem since the factors contributing to a rise in food waste have received insufficient attention. Moreover, consumer behavior towards food waste is commonly ignored, this detrimental habit has become the norm in society. Therefore, this study investigates the factors that influence food waste among Muslim consumers in Selangor, Malaysia. A sample of 384 participants was selected to engage in an online survey administered using Google Forms. It is acknowledged that religion and culture positively impact the food waste behavior of Muslim consumers. The research on the influence of religion and culture on food waste behavior can be utilized to generate initiatives for change and improvement can be implemented to break the habitual practice of wasting. Thus, to effectively reduce food waste, it is necessary to gain a deeper understanding of Muslim consumers' food waste behavior and the factors that influence them. This study is without its limitations. Further research is required to better understand other potential significant determinants of food waste.